2012
DOI: 10.1186/1471-2458-12-125
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner physical violence among women in Shimelba refugee camp, northern Ethiopia

Abstract: BackgroundDomestic violence has unwanted effects on the physical and psychological well-being of women, which have been recognized globally as an important public health problem. Violence perpetrated by intimate partner is one form of domestic violence, a serious human rights abuse and a public health issue, among refugees owing to its substantial consequences for women's physical, mental and reproductive health problems. Because the incidents are under-reported, the true scale of the problem is unknown and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
88
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 19 publications
16
88
3
1
Order By: Relevance
“…Men who have lived for a long period in rural areas have been reported to be more likely to be violent (Burazeri et al, 2005). In addition, a higher proportion of partners in the rural areas consumed alcohol and used psychoactive drugs, both of which have been positively associated with occurrence of violence (Jewkes et al, 2002;Mousavi & Eshagian, 2005;Brisibe, Ordinioha, & Dienye, 2011;Feseha, Gmariam, & Gerbaba, 2012;Kiss et al, 2012). In contrast, more urban than rural residents in the current study reported sexual violence.…”
Section: Discussioncontrasting
confidence: 71%
“…Men who have lived for a long period in rural areas have been reported to be more likely to be violent (Burazeri et al, 2005). In addition, a higher proportion of partners in the rural areas consumed alcohol and used psychoactive drugs, both of which have been positively associated with occurrence of violence (Jewkes et al, 2002;Mousavi & Eshagian, 2005;Brisibe, Ordinioha, & Dienye, 2011;Feseha, Gmariam, & Gerbaba, 2012;Kiss et al, 2012). In contrast, more urban than rural residents in the current study reported sexual violence.…”
Section: Discussioncontrasting
confidence: 71%
“…This is supported by different studies conducted in Ethiopia 21,22,28 . Moreover, other studies explained that perceived male dominancy and female inferiority are the predominant factors that promote practices of gender-based violence 9,31 .…”
Section: African Journal Of Reproductive Health December 2017; 21(4):108supporting
confidence: 70%
“…Studies conducted in different parts of Ethiopia report such high prevalence of gender-based violence as 45%, 76.5%, 64.7%, 31% and 50.8% for South, West, Southwest, North, and Northwest of the country respectively [18][19][20][21][22] . Some cross-sectional studies have been done in Ethiopia on the prevalence, risk factors, and health outcomes of gender-based violence among women [18][19][20][21][22] . However, the views of the communities on gender-based violence are not well explored in Ethiopia in general, and in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…Other than the studies conducted to investigate violence against women as a general population, some studies have focused on specific subgroups of women such as pregnant women, HIV infected women, refugee women, infertile women and slum inhabitants that possibly are more prone either to risk of violence or to violence sequels [17][18][19][20][21][22][23][24][25][26]. Several studies have been done specifically trying to link domestic violence and infertility [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…High proportions of physical violence is repeatedly reported from African countries. In a study on women living in Shimelba refugee camp in Northern Ethiopia most common type of physical violence was slapping (61.6%) followed by throwing objects(19.5%) [19]. Slapping is also reported to be the most common type of physical violence among pregnant women, husbands being the main perpetrators [22].…”
Section: Discussionmentioning
confidence: 99%